A Holistic View of the Missioning Process - Pierce, Kathryn T. (Missiology, 2008)
A holistic view and implementation of the Missioning Process is essential for effective cross-cultural mission ministry for both short-term and long-term missioners. This article will explore the role and responsibilities of the three main players as the missioner moves through the preparation phase, the time of insertion in the new culture and during the re-entry to one's home culture.